BENJARONG IN THE SOUTHERN OF THAILAND: SRIVICHAI BENJARONG NAKHON SI THAMMARA PROVINCE - YODVAREE , ARNAN (Journal of Suan Sunandha Arts and Culture, 2024)
From the study of Benjarong in the Southern of Thailand: a case study of “Srivichai Bencharong”, Nakhon Si Thammarat Province, it was found that the Thammarat of “Srivichai Bencharong It originated from the skill and experience of being a worker from Benjarong factory at Don Kai Dee community. Krathum Ban district Samut Sakhon Province. The product style and pattern have 12 patterns, 1) Pikul flower pattern. 2) mixed flower pattern. 3) Khak flower pattern. 4) lotus pattern.5) Pink lotus flower hook pattern. 6) Cotton rose pattern 7) Yod Thian pattern 8) jasmine pattern 9) Thep Phanom pattern 10) Phum Khao Bin pattern 11) Chakri pattern and 12) Chaba pattern and use of different colors in conjunction with gold water or used from the same color as gold. The main colors are dark green, light green, white, red, orange, pink, yellow, blue, blue, black, black, blue. General products have the characteristics and patterns as in the patterns produced in Ban Don Kai Dee community, lacking a southern identity.